A Model of Work-Based Learning - Joseph A. Raelin (Organization Science, 1997)
A comprehensive model of work-based learning is illustrated combining explicit and tacit forms of knowing and theory and practice modes of learning at both individual and collective levels. The model is designed to bring together epistemic contributions which are typically studied in isolation. The learning types produced from the model represent processes the intersection of which can contribute to the development of a comprehensive theory for integrating learning and work. At the individual level, work-based learning might start with conceptualization which provides practitioners with a means to challenge the assumptions underlying their practice. In experimentation, they engage their conceptual knowledge in such a way that it becomes contextualized or grounded. However, within the world of practice, in applying theoretical criteria or advanced analytical techniques, one confronts technical, cultural, moral, and personal idiosyncrasies which defy categorization. Hence, experience is required to reinforce the tacit knowledge acquired in experimentation. In fact, learning acquired through experience, often referred to as implicit learning, is the foundation for tacit knowledge and can be used to solve problems as well as make reasonable decisions about novel situations. Nevertheless, reflection is required to bring the inherent tacit knowledge of experience to the surface. It thus contributes to the reconstruction of meaning. At the collective level, conceptualization again makes a contribution in informing spontaneous inquiry but is now embedded within the more formal methods of applied science. Scientists seek to describe and explain social reality through the manipulation of theoretical propositions using the rules of hypothetico-deductive logic. The theories of applied science are often not helpful to practitioners, however, unless they are incorporated into practice. This is the purview of action learning wherein real-time experience, especially problems occurring within one's own work setting, constitutes the primary subject matter. As practitioners come together by being involved with one another in action, they may become a community of practice wherein they learn to construct shared understanding amidst confusing and conflicting data. Hence, community of practice returns knowledge back into its context such that groups learn to observe and experiment with their own collective tacit processes in action. Action science is called upon to bring the individuals' and group's mental models, often untested and unexamined, into consciousness. It is a form of “reflection-in-action” which attempts to discover how what one did contributed to an unexpected or expected outcome, taking into account the interplay between theory and practice. Applications of the model can spur conceptual and practical developments that might lead to a comprehensive theory of work-based learning. The discussion takes up such issues as transition links between learning types, their segmentation by function or process, and implications for epistemology. A sample program, incorporating many of the learning types in the model, is demonstrated. The paper argues that all eight types of learning need to be brought into consideration if learners are to achieve proficiency and become critical while learning at work.
Keywords: D23; J21; J24; M12; M53; M54; 330; Theory and practice; Epistemology; Organizational learning; Action learning; Action science; Organizational cognitioin